2021
DOI: 10.1021/acssuschemeng.0c09131
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Aromatic and Ketone Content of Bio-oils as Rejuvenators to Enhance Their Efficacy in Restoring Properties of Aged Bitumen

Abstract: The potential of the bio-oil from the co-pyrolysis of poplar wood and waste tire rubber to revitalize severely aged bitumen was examined by shifting the balance of aromatics and ketones in the bio-oil. Laboratory experiments were performed to compare the revitalization efficiency of bio-oils from the pyrolysis of poplar wood and co-pyrolysis of wood and waste tire rubber. Furthermore, the chemical compositions of the bio-oils from both processes were studied using gas chromatography−mass spectrometry to distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Improved properties also include greater resistance to ageing and stability at high temperatures. The main reason for modifying bitumen with polymers can be summarized as follows 59: To make softer blends at low service temperatures and to reduce cracking To make stiffer blends at high temperatures and to reduce rutting To increase the stability and strength of the asphalt mixtures To improve the abrasion resistance of blends To decrease the oxidation of bitumen and improve ageing resistance To improve the fatigue resistance of blends To reduce the structural thickness of pavements To improve the efficiency and durability To reduce the life costs of the pavements …”
Section: Limitations Of Base Bitumenmentioning
confidence: 99%
“…Improved properties also include greater resistance to ageing and stability at high temperatures. The main reason for modifying bitumen with polymers can be summarized as follows 59: To make softer blends at low service temperatures and to reduce cracking To make stiffer blends at high temperatures and to reduce rutting To increase the stability and strength of the asphalt mixtures To improve the abrasion resistance of blends To decrease the oxidation of bitumen and improve ageing resistance To improve the fatigue resistance of blends To reduce the structural thickness of pavements To improve the efficiency and durability To reduce the life costs of the pavements …”
Section: Limitations Of Base Bitumenmentioning
confidence: 99%
“…Li et al compared the effect of different compositions present in bio-oils on their performance. According to their results, they concluded that rejuvenators containing a high amount of aromatics and alkanes and a lower amount of ketones showed higher efficacy at restoring the properties of aged bitumen . Uz and Gokalp used waste vegetable cooking oil (sunflower oil) as an economical bio-oil to recover aged bitumen after both short-term and long-term aging.…”
Section: Chemical Agingmentioning
confidence: 99%
“…Other works describe the utilization of bio-oil to produce polyols from which polyurethane foams are later achieved with increased tensile strength and thermal stability and higher biodegradability [141][142][143]. Bio-oil in bitumen applications is also reported to possibly increase bitumen performance and reduced binder consumption [3,116,[144][145][146][147][148][149].…”
Section: Applications Of Bio-oil As Chemical Source and Its Refinement Strategiesmentioning
confidence: 99%